EVALUASI PROGRAM ADIWIYATA DI SDN 2 CIJULANG - Azizah, Iftia; Syarip Hidayat; Pidi Mohamad Setiadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to evaluate the implementation of the Adiwiyata Program at SDN 2 Cijulang using the CIPP evaluation model (Context, Input, Process, Product). The program has been implemented since 2022 as an effort to foster environmental awareness and character among students. The findings show that the program planning was carried out participatively, supported by adequate resources, and utilized the school’s surrounding environmental potential. Despite challenges related to budgeting, student awareness, and facility management, the implementation has been comprehensive through daily activities, integration into learning, and collaboration with external parties. The product evaluation reveals that students demonstrate strong understanding and active participation in environmental activities and have successfully developed innovative processed products from school-grown crops with practical and economic value. Overall, the Adiwiyata Program at SDN 2 Cijulang has succeeded in building a sustainable culture of environmental care in the school environment.